Legal Friction of State Civil Apparatus Neutrality in Indonesia - Sarnawa, Bagus (Universitas Muhammadiyah Yogyakarta, 2018)
The State Civil Apparatus (ASN) is the executor of governmental and development duties. Therefore, ASN must be neutral. According to Law No. 5 of 2014, the neutrality of ASN must be free from the influence and intervention of all groups and political parties. In order to maintain the neutrality of the State Civil Apparatus from the influence of political parties and to ensure the integrity, cohesiveness and unity of the State Civil Apparatus, and to focus all attention, mind and energy on assigned duties, ASN is prohibited from becoming a member and / or political party official. Historically, the arrangement of ASN neutrality began during the Old Order period, which the issuance of Presidential Regulation No. 2 of 1959 on the Prohibition of Civil Servants and State Officials in Political Parties in that time. Furthermore, this Presidential Regulation is followed up and extended by Circular Letter of the President of the Republic of Indonesia No. 2 of 1959 concerning on Prohibition of Political Party Membership for State Civil Apparatus that implement state obligation outside his position. Furthermore, in the New Order era, Law No. 8 of 1974 on the Principal of Employee Affairs, while in the Reform Order was issued Law No. 43 of 1999, Civil Servants should be neutral from the influence of all groups and parties and not discriminatory in providing services to the community.